Consensus of discrete-time multi-agent systems with adversaries and time delays - He, Xiongxiong (2014)
This paper studies the resilient asymptotic consensus problem for discrete-time Multi- Agent Systems in the presence of adversaries and transmission delays. The network is assumed to have p loyal agents and n-p adversarial agents, and each loyal agent in the network has no knowledge of the network topology other than an upper bound on the number of adversarial agents in its neighborhood. For the considered networked system, only locally delayed information is available for each loyal agent and also the information flow is directed, a control protocol using only local information is designed to guarantee the realization of consensus with respect to communication graph which satisfies a featured network robustness. Numerical examples are finally given to demonstrate the effectiveness of theoretical results.